Misfits in skyrme-hartree-fock - Erler, J.; Klüpfel, P.; Reinhard, Paul-Gerhard (Journal of Physics G: Nuclear and Particle Physics, 2010)
We address very briefly five critical points in the context of the Skyrme-Hartree-Fock (SHF) scheme: (1) the impossibility of considering it as an interaction, (2) a possible inconsistency of correlation corrections such as, e.g., the centre-of-mass correction, (3) problems of describing the giant dipole resonance (GDR) simultaneously in light and heavy nuclei, (4) deficiencies in the extrapolation of binding energies to super-heavy elements (SHE) and (5) a yet inappropriate trend in fission lifetimes when going to the heaviest SHE. While the first two points have a more formal bias, the other three points have practical implications and wait for solution. © 2010 IOP Publishing Ltd.
CRIS-Team Scopus Importer:2023-07-24